THE DIFFERENCES OF INTRUCTIONAL MEDIA AND COORDINATION IN LEARNING OUTCOMES OF GROUNDSTROKES TENNIS ON NOVICE LEVEL ATHLETES - Dian Pujianto (Program Pascasarjana Universitas Negeri Jakarta, 2017)
AbstractThe purpose of this study was to find out the differences in instructional media and coordination to learning outcomes on tennis groundstrokes of novice athletes. This experimental research with 2 x 3 of factorial design was conducted in the Bengkulu city, Data was collected through groundstrokes tennis test. The analysis of data outcomes was stated (1) demonstration and video tennis training media gave different learning outcomes of groundstrokes tennis on students. (2) demonstration and tennis video game media gave different learning outcomes of groundstrokes tennis on students. (3) video tennis training and tennis video game media gave different learning outcomes of groundstrokes tennis on students. (4) there were differences in instructional media and coordination skill on learning outcomes of groundstrokes tennis on students. (5) demonstration and video tennis training media gave different learning outcomes of groundstrokes tennis on students with high coordination skill. (6) demonstration and tennis video game media gave different learning outcomes of groundstrokes tennis on students with high coordination skill. (7) no learning outcomes differences of groundstrokes tennis between video tennis training and tennis video game media on students with high coordination skill. (8) no learning outcomes differences of groundstrokes tennis between demonstration and video tennis training media on students with low coordination skill. (9) no learning outcomes differences of groundstrokes tennis between demonstration and tennis video game media on students with low coordination skill. (10) video tennis training and tennis video game media gave different learning outcomes of groundstrokes tennis on students with low coordination skill.The results were recommended that video tennis training media should be used to train the skill of groundstrokes tennis on student with low coordination skill, while demonstration media should be used for novices with high coordination skill.Keywords : Instructional Media, Coordination, Groundstrokes.